The Development of Bioethics at The Hospital for Sick Children: From Committee to Integration - Ritchie, Zoe; Turner, Lucie; Anderson, James; Kirsch, Roxanne; Hassanein, Maram; McCradden, Melissa; Chad, Lauren; Lord, Sarah; Zlotnik Shaul, Randi (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Documenting the evolution and experiences of bioethics services contributes to a repository of successes and challenges that can serve as a lasting resource for all involved in bioethics work. This chronology of bioethics at The Hospital for Sick Children (SickKids) in Toronto, Canada, is one such documenting project. It describes events, challenges and successes that contributed to the Bioethics Department’s evolution from an ethics committee to a department increasingly integrated into teams and processes across the organization. Using a mix of primary and secondary sources, including materials prepared for cyclical accreditation surveys, newspaper clippings, books and reports, meeting notes, eyewitness accounts, oral testimonies, video recordings, personal communications, and archival materials, we explore the development and integration of bioethics activities at SickKids and the ways in which staff and colleagues navigated the place and purpose of bioethics within the institution from the early 1980s to the present day. Each hospital-based bioethics resource reflects and contributes to the situated development of bioethics across local, national and international contexts. A focused examination of one department’s development can preserve the contributions of people, practices, and contexts that defined major milestones in its development and shaped its organizational culture. Reflective work of this kind supports bioethics service development, ensures the lessons embedded in institutional knowledge remain accessible to current and future bioethicists, and contributes transferable insights that can inform other services and the broader field of applied bioethics.